Nutrient and mycotoxin content of commercially-sold premixed infant cereals in Malawi - Gilbert, Rachel; Subedi, Binita; Wallingford, Jessica; Wilson, Norbert; Masters, William A. (International Food Policy Research Institute, 2019)
Fortified premixed cereals can help caregivers meet infants’ nutrient needs, when used instead of traditional porridges to complement continued breastfeeding alongside the gradual introduction of nutrient-dense family foods from 6 to 24 months of age. Premixed cereals are widely used in nutrition assistance programs, but commercially-sold brands are often poorly regulated and labeled. This study provides the first combined assessment of nutrient levels and mycotoxins in samples of several commercially-sold premixed cereals (CPC) in Malawi, a country with high burdens of child malnutrition and an active market for CPCs. A sample of CPCs available in markets in central and southern Malawi were tested for macronutrients, iron, and zinc as well as for the presence of aflatoxins and fumonisin. Test results were compared to both the values stated on the CPC labels and available standards. CPC samples largely met moisture, ash, and iron standards set by the Malawi Bureau of Standards (MBS), but only 35, 56, and 39 percent of samples were compliant with Malawi standards for zinc, protein, and fat, respectively. Most locally-made products had aflatoxin and fumonisin levels that exceeded national and international maximum allowable levels for infant foods. Labeled values deviated significantly from test results for all nutrients except protein and zinc. Semi-structured interviews with stakeholders in Malawi highlighted challenges producers of CPCs face in meeting quality standards. Access to CPCs of high and uniform quality is hampered by poor market surveillance and standards enforcement, plus the cost of independent testing and other quality control measures. The introduction and enforcement of better standards for quality control and labeling of commercial complementary foods in Malawi could serve as a model for the other low- and middle- income countries facing similar issues.